(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Time management is a critical skill for nursing students, directly influencing academic performance, stress levels, and future clinical efficiency. Despite its importance, many students struggle to manage their time effectively during their training years. Objectives: This study aimed to assess time management practices among nursing students at Sir C.J. College of Nursing, Hyderabad, and to identify key barriers contributing to poor time management. Methods: A cross-sectional descriptive study was conducted among 121 Bachelor of Science in Nursing students across all academic years. Data were collected using a structured questionnaire covering time management behaviors and perceived barriers. Descriptive statistics and chi-square tests were used for analysis. Results: The findings showed that 72.7% of students consistently completed their daily tasks, and 57.9% prioritized studying over other activities. However, mobile phone usage interfered with study schedules for 34.7% of students. Planning in advance was found helpful by 73.0% of respondents, and 52.9% reported regularly using daily or weekly to-do lists. Major barriers to effective time management included academic workload (52.0%), lack of training in secondary school (31.4%), and limited knowledge of time management strategies (28.1%). Conclusion: While a majority of nursing students reported effective time management habits, a significant number face challenges due to inadequate preparation, academic stress, and digital distractions. Integrating time management training into nursing education and providing academic support could improve overall student performance and readiness for professional responsibilities.